Management Assistance in Financial Management Darussalam Dukuhwaluh Boarding School Based Management Information System - Dewi Laela Hilyatin; Akhris Fuadatis Sholihah; Fatimatuzzahro Fatimatuzzahro (el-Jizya: Jurnal Ekonomi Islam, 2023)
Darussalam Islamic Boarding School as one of the boarding schools whose development is quite rapid is evidenced by the increase in the number of students, supporting facilities and infrastructure, facilities provided, and achievements achieved. Although the achievements obtained are quite good, in terms of data management, pesantren data is still weak, especially pesantren financial data. This service is carried out to assist pesantren in making pesantren database management, especially financial data by building the "SiPontren" application. The Si Pontren application was built by the IAIN Purwoekrto service team, the Pesantren Si Pontren Team, and a team of programmers as partners. The data base has started the input process and in its implementation there are several evaluations carried out to optimize "Si Pontren"